Factors of Income Inequality and their Influence Mechanisms: A Review of the Empirical Literature - Kaasa, Anneli (Journal of Income Distribution®, 2006)
When analyzing the factors of income inequality, first as many factors as possible have to be included in order to obtain valid results. The present article systematizes the factors of income inequality discussed in the pertinent empirical literature into six groups and summarizes the hypotheses about the signs of the influences of the discussed factors on income inequality. Additionally the influences between the factors themselves that form indirect effects on income inequality have to be included. In this article, these influences are discussed and arranged in a system to give an idea about the possible indirect effects on income inequality of the factors discussed in the article.